The Feasibility of the Smart Building Training Kit as Learning Media for Electrical Lighting Installation Practices in Vocational High Schools - Sukir, Sukir; Asnawi, Rustam; Taruno, Djoko Laras Budiyo; Hanif, Naufal Muhammad (Jurnal Edukasi Elektro, 2023)
The purposes of this study are: (1) to produce smart building training kit products, and (2) to find out the feasibility of the smart building trainer kit as a learning medium for Electrical Lighting Installation Practices in Vocational High Schools (VHS). This research employed the research and development (R & D) with the ADDIE model based on Branch (Analyze, Design, Develop, Implement, and Evaluate). The techniques to collect the data included interviews, observations, and questionnaires. The data obtained were analyzed descriptively. The research results show that (1) smart building trainer kit has been produced as a learning tool for Electric Lighting Installation Practices at VHSs with the dimensions of 96 cm in length, 67 cm in height, 25 cm in width at the bottom, and 13 cm at the top; and (2) the developed product was declared very feasible by material experts (95.83%), very feasible by media experts (89.06%), and appropriate by VHS students (80.8%).